2022
DOI: 10.1080/23802359.2022.2139162
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome ofVeronica arvensisand its phylogenomic inference in plantaginaceae

Abstract: Veronica arvensis , which is an annual flowering plant in the plantain family Plantaginaceae, has commonly used as a Chinese herbal medicine to treat malaria in China. Here, the complete plastome of V. arvensis was successfully assembled based on genome skimming sequencing. The plastome of V. arvensis was 149,386 bp in length, comprising a pair of inverted repeats (IR; 24,946 bp) separated by a large single-copy (LSC) region (82,004 bp) and a small singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…S2 ) methods using the cp genomes. The four phylogenetic trees showed the same evolutionary relationships, of which the genetic relationship between Veronica and Neopicrorhiza is the closest, followed by Lagotis and Veronicastrum , this is consistent with previous research results 41 43 . While that with related genus species under Scrophulariaceae is the farthest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…S2 ) methods using the cp genomes. The four phylogenetic trees showed the same evolutionary relationships, of which the genetic relationship between Veronica and Neopicrorhiza is the closest, followed by Lagotis and Veronicastrum , this is consistent with previous research results 41 43 . While that with related genus species under Scrophulariaceae is the farthest.…”
Section: Discussionsupporting
confidence: 91%
“…Recent taxonomy studies have utilized cp genomes to assess the genetic relationship between related species [37][38][39][40] . The basic groups of nine species in this genus range in size variations from 149,386 to 152,319 bp, indicating that each of these species has significantly different cp gene sizes 13,[41][42][43] . A comparative analysis of the cp genomes in V. anagallis-aquatica and V. undulata showed that they contain highly conserved structures and genes as well as the same protein-coding genes, tRNA, and rRNA.…”
Section: Discussionmentioning
confidence: 99%
“…attenuata shows a quadripartite structure similar to that in the majority of other angiosperms (Liu et al. 2022 ), consisting of a pair of inverted repeats (IRs), a small single-copy (SSC) region, and a large single-copy (LSC) region. The phylogeny reconstructed from complete plastomes revealed that E. rubiginosa var.…”
Section: Discussionmentioning
confidence: 97%
“…The genomic structure of P. hadiensis consists of a pair of IRs, an SSC region, and an LSC region similar to that in the majority of other angiosperms (Liu et al. 2022 ). The phylogenetic results indicated that P. hadiensis exhibited the closest relationship with Isodon in the subfamily Nepetoideae.…”
Section: Discussionmentioning
confidence: 99%